ChemInform Abstract: Regioselective Azidotrimethylsilylation of Carbohydrates and Applications Thereof. Issue 19 (18th April 2013) - Rao L, Mallikharjuna; Yousuf, Syed Khalid; Mukherjee, Debaraj; Taneja, Subhash Chandra
Abstract This method uses Mitsunobu conditions and trimethylsilyl azide to substitute primary alcohol moieties of carbohydrates with azide groups while secondary alcohol moieties are silylated.